E-Learning Utilizing Schoology: Teaching Theory of Relativity Using Online - Dadan Sumardani; Agustiani Putri; Nur Ichsan Sumardani (Risenologi, 2020)
Physics is not only learning through the presentation of concepts or formulas, but many events can be understood through various learning media. Evidently, students better understand the material if they can interact directly with the topic of the lesson. In addition, the rapid internet makes teachers are required to actively develop learning media. This research aims to develop physics learning using E-Learning learning media on the Special Theory of Relativity material for high school students in class XII. This study uses research and development methods that refer to the ADDIE model. This research is limited to making applications. Based on the results of research, this development has produced products that function well and present features that support student learning. Available features include quizzes, learning videos, materials and simulations that students can access. E-learning developed using Schoology can support learning through the online platform. E-learning using Schoology can display the stages of stimulus that can be determined by educators when using this e-learning. Therefore, e-learning learning that utilizes Schoology on relativity material can be designed and developed according to the needs of teachers and students in the learning process in class.